Arrhythmogenic Cardiomyopathy—Further Insight into the Clinical Spectrum of Desmoplakin Disease - Joanne Simpson; Joan Anusas; Denise Oxnard; Sylvia Wright; Ruth McGowan; Caroline Coats (Cardiogenetics, 2021)
Arrhythmogenic cardiomyopathy is a familial heart muscle disease characterized by structural, electrical, and pathological abnormalities. Recognition of left ventricular (LV) involvement in arrhythmogenic right ventricular cardiomyopathy (ARVC) has led to the newer term of arrhythmogenic cardiomyopathy (ACM). We report on a family with autosomal dominant desmoplakin (DSP) related ACM to illustrate the broad clinical spectrum of disease. The importance of evaluation of relatives with cardiac magnetic resonance imaging and consideration of genetic testing in the absence of Task Force diagnostic criteria is discussed. The practical and ethical issues of access to the Guthrie collection for deoxyribonucleic acid (DNA) testing are considered.